tangaloomaflyer
New member
- Joined
- Apr 24, 2016
- Messages
- 13
OK, here's another one:
For equation x2 = 2x -3 with root p
show that p3 = p-6
So I've re-arranged to get x2 -2x +3
The roots are complex: 1+(i*sqrt2) and 1-(i*sqrt2)
I can't see how p3 = p-6
For p3 i get:
-1+(i*sqrt2) or 3-(3*i*sqrt2)
For p-6 I get:
(i*sqrt2) - 5 or (i*sqrt2) -4
Where to go from here?
For equation x2 = 2x -3 with root p
show that p3 = p-6
So I've re-arranged to get x2 -2x +3
The roots are complex: 1+(i*sqrt2) and 1-(i*sqrt2)
I can't see how p3 = p-6
For p3 i get:
-1+(i*sqrt2) or 3-(3*i*sqrt2)
For p-6 I get:
(i*sqrt2) - 5 or (i*sqrt2) -4
Where to go from here?